School Finance and Reform in Delaware: A Summary - Yasser A. Nakib (Educational Considerations, 1997)
Delaware, although a small state with less than 20 school districts, is no different from other states in the dynamics and complexities of the political structure that has the most profound impact on educational policies in general and on public school finance in particular.